Pengaruh Harga,Word Of Mouth,Promosi Dan Kualitas Produk Terhadap Keputusan Pembelian Usaha Umkm Nasi Goreng Simpang Rantau Lama Jalan Ahmad Yani Rantau Prapat - Abdul Hamid; Yudi Prayoga; Pitriyani Pitriyani (STIE AMKOP, 2023)
This study aims to analyze the effect of price, word of mouth, promotion and product quality on product purchasing decisions for UMKM business of Nasi Goreng Simpang Rantau Lama Jalan Ahmad Yani Rantau Prapat. This type of research is quantitative. Data collection techniques used in this research are observation, documentation and questionnaires using a Likert scale. The population contained in this study are consumers, amounting to 100 people. Samples were taken using the slovin formula. Thus, all populations become research objects, namely as many as 100 people. The results showed that price, promotion and product quality simultaneously had a positive and significant effect on product purchasing decisions for small and medium-sized fried rice businesses at Simpang Rantau Lama Jalan Ahmad Yani Rantau Prapat. Meanwhile, the Word Of Mounth variable has no positive but significant effect on product purchasing decisions for the Umkm Fried Rice Business at Simpang Rantau Lama Jalan Ahmad Yani Rantau Prapat. The R Square value from the analysis of the coefficient of determination is 0.758, meaning that employee performance can be explained by the variable price (X1), word of mount (X2), promotion (X3) and product quality (X4) of 75.8%, while the remaining is 24. 1% can be explained by other variables not examined in this study. Keywords: Price, Word Of Mouth, Promotion, Product Quality, Purchase Decision